(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2014)
In the article we try to find out the specifics of artistic interpretation and reproducing of ideological and aesthetic conception of the author, reconstructed with the subtext, by analyzing of the stories "Red Army soldier" and "Grandfather Yavtuh" by Philip Kapelhorodskiy.